2017
DOI: 10.1177/0032329217704432
|View full text |Cite
|
Sign up to set email alerts
|

Colonial Legacy of Gender Inequality: Christian Missionaries in German East Africa

Abstract: Nutzungsbedingungen: Dieser Text wird unter einer Deposit-Lizenz (Keine Weiterverbreitung-keine Bearbeitung) zur Verfügung gestellt. Gewährt wird ein nicht exklusives, nicht übertragbares, persönliches und beschränktes Recht auf Nutzung dieses Dokuments. Dieses Dokument ist ausschließlich für den persönlichen, nicht-kommerziellen Gebrauch bestimmt. Auf sämtlichen Kopien dieses Dokuments müssen alle Urheberrechtshinweise und sonstigen Hinweise auf gesetzlichen Schutz beibehalten werden. Sie dürfen dieses Dokume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 29 publications
0
14
1
Order By: Relevance
“…Earlier studies have found Protestant missions to promote education more effectively than Catholic missions (Cogneau and Moradi 2014 ; Gallego and Woodberry 2010 ). Other studies point at geographic nuances regarding the long-term effects of Christian missions (Montgomery 2017 ).…”
Section: Literaturementioning
confidence: 99%
“…Earlier studies have found Protestant missions to promote education more effectively than Catholic missions (Cogneau and Moradi 2014 ; Gallego and Woodberry 2010 ). Other studies point at geographic nuances regarding the long-term effects of Christian missions (Montgomery 2017 ).…”
Section: Literaturementioning
confidence: 99%
“…At the same time, black women are spatially entangled with global feminist struggles through the internationalisation of Western gender relations by the women’s equality movements, development institutions, and the Christian religion. Using digital technologies, Montgomery’s (2017) research in Tanzania demonstrates how the legacy of German Catholic missionaries continues to produce unequal gender educational outcomes in the contemporary period. Studying black women requires the adoption of a transnational intersectional scholarship and, according to Mollett and Faria, can “deepen not just critical race feminism and race sexuality studies within feminist geography, but also extend new ways of thinking about enduring spatialities” (2018, p. 573).…”
Section: Studying Lives Lived Differentlymentioning
confidence: 99%
“…52 In this special issue, Montgomery advances the literature on colonial legacies of Christian missionaries. 53 Although a substantial body of work has already documented the general benefits of Christian missionary activity on human capital development, he looks at the extent to which exposure to missionary schooling affected gender inequality in educational attainment in the long term. Using detailed school-level information from colonial Tanzania and geographically referenced modern-day outcome measures of educational attainment, he shows that both Catholic and Protestant missionaries had positive effects on educational attainment.…”
Section: Noninstitutional Interventions and Channels Of Transmissionmentioning
confidence: 99%